PERBEDAAN PENGARUH TERAPI SINAR INFRA MERAH DAN BACK EXERCISE TERHADAP NYERI PUNGGUNG BAWAH DENGAN FLEKSIBILITAS TULANG BELAKANG DITINJAU DARI JENIS KELAMIN - Eko Budi Prasetyo; Sugiyanto .; Agus Kristiyanto (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2016)
The purpose of this study to determine differences in the effect of back exercises to increase fleksibilitas of the spine, the lower back pain and spinal fleksibilitas, and to investigate the interaction between type of therapy, low back pain, spinal fleksibility and gender. Type of research is that the study is a quasi-experimental,with a pretest - posttest design approach. With the method of taking samples is purposive incidental sampling through inspection procedures to establish the diagnosis of lower back pain. The results in this study are reduction in lower back pain and increase spinal fleksibility but there is no effect and a significant interaction between the type of physical therapy to increase fleksibility anddecrease lower back pain , then there is no significant difference between the type of therapy to lower back pain and spinal fleksibility, but there are significant differences in the increase in fleksibilitas if the terms of gender .Based on the conclusions obtained the following results : (1) The type of physical therapyinfrared and William Flexi Exercise better increase the fleksibility of the spine and lower back pain compared with other types of physical therapy infrared and Mc . Kenzie exercise, (2) There are differences increase the fleksibility of the spine by gender, and obtained the same result for lower back pain by gender , (3)there is no significant interaction between the type of physical therapy tofleksibility, lower back pain an gender